Linearity improvement of 5.2-GHz CMOS up-conversion mixer for wireless applications - Sohiful Anuar, Zainol Murad, Dr.; Mukhzeer, Mohamad Shahimin, Dr.; Pokharel, Ramesh Kumar, Prof.; Kanaya, Haruichi, Assoc. Prof.; Yoshida, Keiji, Prof (John Wiley & Sons, Inc., 2013)
Link to publisher's homepage at http://onlinelibrary.wiley.com/